Softwares/simuladores virtuais como recurso didático no ensino de física - Coelho, Raeleson Lima (Brasil, 2019)
This paper aims to conduct a bibliographical study on the importance of technological resources as an aid to the teaching of physics. Three software simulators stood out because they have strong potential for didactic use, focusing on teaching the discipline of Physics. They consist of platform technology features that allow online and offline access. The use of technological resources has been one of the motivating levers for the formal teaching-learning process, especially in the area of ​​physics, as it is notoriously attractive and easy to handle. This project aims to show applications through virtual software / simulators and the insertion of the use of these computational technologies in physics teaching. In this sense, we try to answer the following question: can the use of virtual simulators and software, in fact, contribute to the improvement of learning of physics contents? It is believed that using virtual simulators and software, the teacher can achieve a more effective participation of the students, exploring the content in a more dynamic and interactive way, as a consequence, enhancing the teaching of the worked content.